Reading and Writing Motivation of Third to Sixth Graders. Issue 1 (2nd January 2020) - Vaknin-Nusbaum, Vered; Nevo, Einat; Brande, Sigalit; Gambrell, Linda
Abstract : Motivational questionnaires (MRP-R and MWP) were used to investigate reading and writing motivation (self-concept and value) among 252 Hebrew-speaking students in third to sixth grade. CFA for reading and writing motivation revealed a close to reasonable fit, for the total sample and by gender. It yielded a low fit across the four grade levels. Four main results were obtained: (1) reading and writing motivation remained at the same level in all four grades; (2) reading motivation was higher than writing motivation; (3) students' self-concept was higher than value in both reading and writing; (4) value of reading was higher than value of writing. It is suggested that educators take into account the importance of increasing reading and writing motivation in the early years of elementary school, before motivation stabilizes in third grade. Additionally, attention should be paid to the value that students attach to reading and especially writing, since it may be related to their involvement in reading and writing tasks. Further examination and development of the questionnaire assessing writing motivation is required. More implications of the results for developmental aspects of reading and writing motivation are discussed.